Research Progress, Challenges, and Breakthroughs of Organoids as Disease Models - Huang, Yisheng; Huang, Zhijie; Tang, Zhengming; Chen, Yuanxin; Huang, Mingshu; Liu, Hongyu; Huang, Weibo; Ye, Qingsong; Jia, Bo (Frontiers in Cell and Developmental Biology, 2021)
Traditional cell lines and xenograft models have been widely recognized and used in research. As a new research model, organoids have made significant progress and development in the past 10 years. Compared with traditional models, organoids have more advantages and have been applied in cancer research, genetic diseases, infectious diseases, and regenerative medicine. This review presented the advantages and disadvantages of organoids in physiological development, pathological mechanism, drug screening, and organ transplantation. Further, this review summarized the current situation of vascularization, immune microenvironment, and hydrogel, which are the main influencing factors of organoids, and pointed out the future directions of development.